2022
DOI: 10.1093/asj/sjac318
|View full text |Cite
|
Sign up to set email alerts
|

Basic Consideration for Facial Aging: Age-Related Changes of the Bony Orbit and Orbicularis Oculi Muscle in East Asians

Abstract: Background Age-related changes in the periocular areas are mainly caused by anatomical changes of the bony orbit and orbicularis oculi muscle (OOM). To achieve effective rejuvenation, it is necessary to understand these anatomical changes according to age. Objectives We analyzed the configuration of the bony orbit and OOM using computed tomography (CT) and evaluated the effects of aging on these structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This study showed that the SMAS, like muscles of facial expression, 8 become thinner with aging, suggesting that it is involved in mechanisms of facial aging. In the future, if the aging mechanism of SMAS is elucidated in more detail, it may be possible to apply it to nonsurgical facial rejuvenation therapy and help develop more effective and safer facelift surgeries.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…This study showed that the SMAS, like muscles of facial expression, 8 become thinner with aging, suggesting that it is involved in mechanisms of facial aging. In the future, if the aging mechanism of SMAS is elucidated in more detail, it may be possible to apply it to nonsurgical facial rejuvenation therapy and help develop more effective and safer facelift surgeries.…”
Section: Discussionmentioning
confidence: 61%
“…In 2019, Okuda et al 5 reported that SMAS laxity increases due to aging. Furthermore, in a report by Okuda et al 8 in 2022, it was shown that the orbicularis oculi muscle became thinner due to aging. Additionally, it has been shown that the lateral part of the orbicularis oculi muscle, lateral canthal tendon, and major zygomatic muscle droop with aging when standing.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations